Adjacent Terrestrial Landscapes Impact the Biogeographical Pattern of Soil Escherichia coli Strains in Produce Fields by Modifying the Importance of Environmental Selection and Dispersal - Liao, Jingqiu (Appl Environ Microbiol, 2021)
High-quality habitats for wildlife (e.g., forest) provide essential ecosystem services while increasing species diversity and habitat connectivity. Unfortunately, the presence of such habitats adjacent to produce fields may increase risk for contamination of fruits and vegetables by enteric bacteria, including Escherichia coli. E. coli survives in extrahost environments (e.g., soil) and could be dispersed across landscapes by wildlife. Understanding how terrestrial landscapes impact the distribution of soil E. coli strains is of importance in assessing the contamination risk of agricultural products. Here, using multilocus sequence typing, we characterized 938 E. coli soil isolates collected from two watersheds with different landscape patterns in New York State, USA, and compared the distribution of E. coli and the influence that environmental selection and dispersal have on the distribution between these two watersheds. Results showed that for the watershed with widespread produce fields, sparse forests, and limited interaction between the two land use types, E. coli composition was significantly different between produce field sites and forest sites; this distribution appears to be shaped by relatively strong environmental selection, likely from soil phosphorus, and slight dispersal limitation. For the watershed with more forested areas and stronger interaction between produce field sites and forest sites, E. coli composition between these two land use types was relatively homogeneous; this distribution appeared to be a consequence of wildlife-driven dispersal, inferred by competing models. Collectively, our results suggest that terrestrial landscape attributes could impact the biogeographic pattern of enteric bacteria by adjusting the importance of environmental selection and dispersal. IMPORTANCE Understanding the ecology of enteric bacteria in extrahost environments is important for the development and implementation of strategies to minimize preharvest contamination of produce with enteric pathogens. Our findings suggest that watershed landscape is an important factor influencing the importance of ecological drivers and dispersal patterns of E. coli. Agricultural areas in such watersheds may have a higher risk of produce contamination due to fewer environmental constraints and higher potential of dispersal of enteric bacteria between locations. Thus, there is a perceived trade-off between priorities of environmental conservation and public health in on-farm food safety, with limited ecological data supporting or refuting the role of wildlife in dispersing pathogens under normal operating conditions. By combining field sampling and spatial modeling, we explored ecological principles underlying the biogeographic pattern of enteric bacteria at the regional level, which can benefit agricultural, environmental, and public health scientists who aim to reduce the risk of food contamination by enteric bacteria while minimizing negative impacts on wildlife habitats.